METHODICAL APPROACHES TO DIAGNOSIS OF FORMATION AND ENSURING SUSTAINABLE DEVELOPMENT OF A SMART CITY (INNOVATIVE ECONOMY, 2021)
Kolomechiuk V.V. METHODICAL APPROACHES TO DIAGNOSIS OF FORMATION AND ENSURING SUSTAINABLE DEVELOPMENT OF A SMART CITYPurpose. The aim of the article is to improve the methodological approach to the diagnosis of the processes of formation and sustainable development of a smart city, in particular, the formation of a logical and structural approach to this process.Methodology of research. The study uses generally accepted methods in economics: monographic, theoretical and comparative analysis – to reveal the conceptual foundations of the formation and sustainable development of a smart city; analysis and synthesis, system and structural, abstract and logical, statistical groupings – to improve methodological approaches to the diagnosis of the formation and ensure the sustainable development of a smart city.Findings. The analysis of theoretical sources of Ukrainian and foreign scientists concerning the definition and diagnosis of sustainable development of a smart city was conducted. It is established that there is no methodical approach to the diagnosis of sustainable development of a smart city, which is based on statistical observations of the State Statistics Committee of Ukraine. The author’s methodical approach to diagnostics of the process of smart city development is proposed, which, in contrast to the existing ones, covers the consistent implementation of research stages at the macro, meso, and micro levels. The necessity of using a set of statistical data and mathematical methods in the process of developing directions for improving the efficiency of strategic management of sustainable development of a smart city is substantiated.Originality. The methodological approach to the diagnosis of sustainable development of a smart city has been improved, which, in contrast to the existing ones, covers the consistent implementation of research stages at the macro, meso, micro levels: strategic analysis and assessment of sustainable development of smart cities in Ukraine at the macro and meso levels; analysis of the effectiveness of the use of the existing potential for sustainable development of smart cities at the micro level; modelling, development of directions of increase of efficiency of use of available potential and formation of the organizational and economic mechanism of sustainable development of smart cities.Practical value. The application of the proposed methodology will contribute to the development of organizational and economic principles of building a mechanism for managing the development of a smart city.Key words: sustainable development, smart city, diagnostics, organizational and economic mechanism.
Keywords: Key words; sustainable development; smart city; diagnostics; organizational and economic mechanism.